Public Health Center Performance during Covid-19 Pandemic: What are The Contribution of Knowledge Sharing, Work Motivation, Transformational Leadership and Organizational Citizenship Behavior? - Kurniasih, Denok; Setyoko, Paulus Israwan; Saputra, Anggara Setya (Journal of Industrial Engineering & Management Research, 2022)
The aim of this study is to investigate the correlation of transformational leadership and performance, organizational citizenship behavior (OCB) and performance, motivation and performance and knowledge and performance of public health center. This research method is a quantitative survey, analysis and data processing using structural equation modeling (SEM) with a data processing tool is SmartPLS 3.0 software. Respondent in this reseact is 290 hospital staff and selected using simple random sampling. The questionnaire data is distributed online through social media. The stages of data analysis are analyzing validity, reliability, coefficient of determination and hypothesis testing, then conclusion. The independent variables in this study are knowledge sharing, work motivation, transformational leadership and organizational citizenship behavior and the dependent variable is public health center performance. The result of this study is transformational leadership has a positive and not significant effect on motivation of Public health center employees. Knowledge sharing has a positive and not significant effect on the work motivation of Public health center employees. OCB has a positive and not significant effect on the performance of employees. Motivation has a positive and not significant effect on the performance of employees.